Structure analysis of the thermal energy spectrum generated during stimulation of organic matter by an electromagnetic field. Issue 1 (February 2021) - Popardowski, E; Kiełbasa, P; Dróżdż, T.; Rad, M
Abstract: The article presents the spectral characteristics of the temperature distribution in an induction coil which is an actuator in the technology of electromagnetic stimulation of organic matter and in the technology of elimination of undesirable microorganisms. The rate and method of heating the coil were precisely determined depending on the magnitude of the magnetic induction and the stimulation time of the material as well as the amount of flow of the coil cooling agent. Based on the experiment, the structure of the exposure time and the structure of the distribution of biological material in the working part of the coil were determined. Furthermore, the degree of cooling was determined so as to eliminate the uncontrolled momentary temperature amplitude on the course of the organic matter stimulation process.